Development of A Flipbook-Based Problem Based Learning Science E-Module on The Human Circulatory System to Increase Learning Motivation and Critical Thinking Skills of 8th Grade Students - Purwendri, Rina; Nurohman, Sabar; Sumarhadi, Anas (Ridwan Institute, 2025)
This study aims to develop a flipbook-based science e-module using Problem-Based Learning (PBL) to enhance critical thinking skills and learning motivation of grade VIII students on human circulatory system material. This research employed Research and Development (R&D) methodology using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation phases. The research subjects included 33 students in the experimental class and 33 students in the control class at SMP Negeri 14 Yogyakarta. Data collection instruments included validation sheets, practicality questionnaires, critical thinking skills tests, and learning motivation questionnaires. The research design used a quasi-experimental pretest-posttest control group design. Results showed that the developed e-module achieved very feasible category in material and media aspects with scores of 3.88 and 3.95 respectively. Practicality assessment by science teachers and students showed very practical category with a score of 3.80. Effectiveness testing using MANOVA showed significant differences (p = 0.000 < 0.05) between experimental and control groups. The N-gain scores were 0.70 (high category) for critical thinking skills and 0.45 (moderate category) for learning motivation in the experimental group, compared to 0.44 (moderate) and 0.29 (low) respectively in the control group. The effect size analysis using Cohen's d showed large effects for both variables (d = 0.89 for critical thinking; d = 1.73 for learning motivation). The flipbook-based science e-module with PBL approach proved effective in enhancing students' critical thinking skills and learning motivation on human circulatory system material.